The emergence of a knowledge-based theory of internationalisation. (1st December 2015) - Welch, Lawrence S.
Abstract : This paper charts the development of the knowledge-based theory of internationalisation, driven particularly by early research at the University of Uppsala, led by Sune Carlson. Information and knowledge, allied with an interest in the associated effect on risk and uncertainty, were components of a process perspective. Its essence was a focus on the restraining effects of a lack of knowledge as decision-makers contemplated international market entry or expansion requiring a commitment of resources in various forms, in different types of foreign operations (such as exporting, licensing and foreign direct investment). Lack of knowledge of a prospective foreign market (of its characteristics, culture, ways of doing business) was seen to create uncertainty so that firm decision-makers would be less prepared to commit resources. This situation was bound to change as a firm conducted operations in the foreign market and acquired experiential knowledge (learning by doing), which made the foreign market less of a mystery, in the process lowering uncertainty. As the learning process unfolded, and expanded opportunities were perceived, at some stage the firm might be prepared to undertake additional commitments to the foreign market. Empirical research at Uppsala, and in Finland, had shown a pattern of gradual expansion of foreign commitments by internationalising firms. In terms of theoretical development, a key step was relaxation of the assumption of perfect knowledge used in economics (not without critique), noted by Don Lamberton in 1974. Following the development of internationalisation theory in the 1970s, there was a range of extensions to the basic theory, such as the role of networks, the nature of inward–outward connections, and the need for knowledge to pass over language hurdles in the process of international transmission – within and outside the firm. In one sense, the internationalisation of companies was a perfect research site for an exploration of the role of information and knowledge in firm behaviour, given the additional exigencies of the diverse and demanding information environment that is the international arena.